A Study of Metallo Beta Lactamase Producing Clinical Isolates of Pseudomonas aeruginosa - Mohite SL (Online Journal of Health & Allied Sciences, 2014)
Introduction: The emergence and rapid spread of multidrug resistant Pseudomonas aeruginosa causing nosocomial infections is a great concern worldwide. Detection of MBL is also a challenge for routine microbiology laboratories, since there are no standardized methods for MBL detection. The present study was conducted at our hospital with an aim to know the prevalence of metallo beta lactamase producing Pseudomonas aeruginosa, to know MIC of various antibiotics, transfer of drug resistance and predisposing factors for infection with MBL strain. Material and Methods: A total of 608 clinical isolates were tested for the presence of metallo beta lactamase enzyme from Oct 2008 to Sept 2013. Imipenem resistant Ps. aeruginosa isolates were selected for the presence of MBL by Imipenem – EDTA combined disc test, Imipenem – EDTA double disc synergy test (DDST), EDTA disk potentiation test using Ceftazidime, Ceftizoxime, Cefepime, Cefotaxime and MBL E- Test. Result: Out of 608 clinical isolates 91 (14.96%) were resistant to imipenem and 81 (13.32%) were MBL positive by initial two tests. 76(83.51%) were positive by EDTA disk potentiation test using Ceftazidime, Ceftizoxime, Cefepime, Cefotaxime and 63 (69.23%) were positive by E- test. It is observed that 62/81(76.54%) of MBL producing Pseudomonas isolates could transfer the resistance of imipenem to the recipient E. coli J53 AZR strains at 370C. The prevalence of MBL producing Pseudomonas aeruginosa was 81/608 (13.32%). Conclusion: The early detection of MBL producing Pseudomonas aeruginosa may help in appropriate antimicrobial therapy and avoid the development and dissemination of these multidrug resistance strains. Hence all Pseudomonas aeruginosa isolates resistant to imipenem should be screened for MBL production.